Comparison of lower limb and trunk kinematics between markerless and marker-based motion capture systems - Perrot, M. A.; Pizzari, T.; Cook, J.; McClelland, J. A. (Gait and Posture, 2017)
Three dimensional (3-D) motion capture systems are used by researchers and clinicians to analyze the kinematics of human movement. Traditional marker based systems are time consuming and limit the size of studies. Markerless 3-D systems are quicker to use but the differences between data captured in each system is unclear. Aim: To examine the relationship of kinematic data captured by marker based and markerless motion capture systems. Methods: Movement was assessed in two tests: a simple knee flexion test and single leg squat with a marker based protocol (Vicon) and a markerless protocol (Organic Motion). Results: There was no significant difference between protocols in knee flexion angle (p = 0.33). In single leg squat there was no significant difference in 9 of 13 clinically relevant joint angles in the change in angle from the start to the peak of squat. There were significant differences in the angle at the peak of the squat for 9 of 13 joint angles. Discussion: This study provides evidence that a marker-based and a markerless protocol report similar ranges of change in angle from the start of a squat to peak squat in the pelvis and lower limb in single leg squat. Specific joint angles should not be compared between protocols.